Airborne microplastics: A review of current perspectives and environmental implications. (1st May 2022) - Shao, Longyi; Li, Yaowei; Jones, Tim; Santosh, M.; Liu, Pengju; Zhang, Mengyuan; Xu, Liang; Li, Weijun; Lu, Jing; Yang, Cheng-Xue; Zhang, Daizhou; Feng, Xiaolei; et al.
Abstract: Microplastics (MPs), as an entirely anthropogenic type of pollution, are considered to be stratigraphic markers of the Anthropocene Epoch, and have become of increasing public concern over the past decade. Recent studies have revealed that the atmosphere is an efficient medium to disseminate MPs from their sources to remote mountains and marine areas. However, current research on atmospheric MPs (i.e. airborne MPs) is generally less highlighted than MP water and soil pollution studies due to the lack of standard methods for the identification and quantification of atmospheric MPs. This paper reviews the published literature on airborne MPs, gives an overview of the advantages and disadvantages of current airborne MPs collection techniques, extraction methods and identification (i.e., 'passive' and 'active' sampling, density separation and visual identification), and lays a foundation for future studies. The physical and chemical characteristics, classification, spatial and temporal scale distributions, sources, transport, and environmental impacts of airborne MPs are summarized. There are substantial research gaps in the quantification of airborne MPs and the exploration of toxicity mechanisms of inhalable MPs. The establishment of accredited methods is an urgent challenge for a better understanding on airborne MPs and their environmental and health effects. As one of the constituents in many aerosols, airborne MPs should be treated as a recognized pollutant for long-term monitoring, and the factors that specifically affect airborne MPs could be better addressed by means of the characterization of individual MPs. In the future, the effects and interaction of MPs in the atmosphere, lithosphere and hydrosphere are also of critical importance. Graphical abstract: Image 1 Highlights: Atmospheric pollution by airborne microplastics is of increasing concern. Research methods require meaningful comparisons between different studies. Airborne microplastics can lead to the 'fiber paradigm' and bioreactivity. The atmosphere is one of the main pathways for microplastic transport. There is a need for a comprehensive inventory of airborne microplastics.